2019
DOI: 10.3390/app9030578
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Thermal Properties and Enzymatic Degradability of Chiral Polyamide-Imides Films Based on Amino Acids

Abstract: Six kinds of chiral polyamide-imides (PAI3a-3f) have successfully been synthesized via direct polycondensation. The thermal properties of the materials were evaluated by the gravimetric analysis (TGA) and differential scanning calorimetry (DSC). A thermal test was conducted and showed that the polymers have good thermal stability. The Tg values were affected by the volume effect of the side groups, the internal plasticizing effect and the isolation effect. Polyamide-imides (PAIs) with L configuration showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, degradation studies under enzymatic conditions were performed to confirm the polymers’ degradability under milder and biologically relevant conditions. Polymer degradation protocols using proteinase K as an enzyme were reported in the literature by several groups because it is suitable for a wide range of different substrates. , Therefore, dPMeOx was treated with proteinase K at 37 °C for 30 days in a PBS solution. The 1 H NMR spectrum of dPMeOx after the treatment with proteinase K, presented in Figure , confirmed the partial degradation of the polymer, moreover supported by a shift in the SEC elugram toward lower molar masses (Figure SI27).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, degradation studies under enzymatic conditions were performed to confirm the polymers’ degradability under milder and biologically relevant conditions. Polymer degradation protocols using proteinase K as an enzyme were reported in the literature by several groups because it is suitable for a wide range of different substrates. , Therefore, dPMeOx was treated with proteinase K at 37 °C for 30 days in a PBS solution. The 1 H NMR spectrum of dPMeOx after the treatment with proteinase K, presented in Figure , confirmed the partial degradation of the polymer, moreover supported by a shift in the SEC elugram toward lower molar masses (Figure SI27).…”
Section: Resultsmentioning
confidence: 99%
“…PAI 1 that has the largest weight loss showed only the ether-bond peak and barely any others, which also indicated significant degradation. According to our previous studies on PAIs containing a single amino acid, the difference in amino acid chirality has only a small effect on the degradation of the polymers [ 22 ]. But the configuration of amino acids has a great influence on polymers degradation after introducing peptide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the degradation properties of PAIs are improved due to the introduction of natural chiral sections, which is obviously of great significance for development of high-performance, high-processability, and biodegradable polymer materials [ 19 , 20 , 21 ]. However, most of the amino acid-based chiral polymers so far used natural L -α-amino acid-based products as monomers and always introduced independent amide bonds in the main chain of the chiral polymers [ 19 , 22 ]. Studies on peptide-containing chiral polymers have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral diacid monomers (2a–2d′) were synthesized by the condensation of various amino acids and PMDA according to our previous works (see step 1 in Scheme 1 ) [ 21 , 22 , 23 , 24 ]. The yields were obtained by calculating the weight ratios of the materials before and after the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The main purpose of this paper is to check the influence of the side group structure and main chain configuration on the properties of PEI. By controlling the types of amino acids incorporated into PEI, eight kinds of PEIs with different side groups or configurations were synthesized, and the influence of amino acids structure and configuration on the thermal performance and degradability of PEI was evaluated through thermal test and degradation experiment [ 20 , 21 , 22 ]. Through comparisons with the degradable polyimide (PI) previously studied by our group [ 20 , 21 ], we found that PEI was degraded more in a shorter period of time, illustrating that the introduction of an ester bond can improve the degradation property of PI.…”
Section: Introductionmentioning
confidence: 99%